DELINEATING THE RHETORIC? THE INTERSECTION OF RETRIBUTIVE AND RESTORATIVE JUSTICE IN INTERNATIONAL SENTENCING - Oriola O. Oyewole (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2022)
A large and growing body of literature has investigated victim participation at the International Criminal Court. Hence, an increasing number of published studies describe victims' participatory roles and their evolution. However, literature is scarce on managing victims' rights and interests during sentencing and on the impact of victims' involvement in sentencing decisions. For example, victims have interests in reparations, justice, truth and sentencing. Knowledge of restorative justice in criminal sentencing is important for an understanding of how victims navigate criminal trials, especially regarding their perceptions of the sentencing. Using a case analysis, this article critically examines the interaction of retributive and restorative justice vis-à-vis victims’ positions during sentence hearings and reviews. Abstrak: Sejumlah besar literatur telah menyelidiki partisipasi korban di Pengadilan Kriminal Internasional. Oleh karena itu, semakin banyak penelitian yang diterbitkan menggambarkan peran korban selama partisipasi korban dan evolusinya. Namun, literatur tentang pengelolaan hak dan kepentingan korban selama hukuman dan dampak keterlibatan korban pada keputusan hukuman masih terbatas. Misalnya, korban memiliki kepentingan dalam reparasi, keadilan, kebenaran dan hukuman. Pengetahuan tentang keadilan restoratif dalam pemidanaan penting untuk memahami bagaimana korban menjalani persidangan pidana, terutama mengenai persepsi mereka tentang hukuman. Dengan menggunakan analisis kasus, artikel ini secara kritis mengkaji interaksi keadilan retributif dan restoratif vis-à-vis posisi korban selama pemeriksaan dan peninjauan hukuman. Kata Kunci: Hukuman Internasional, Pemidanaan, Reintegrasi, Korban, Pengurangan Hukuman, Keadilan Restoratif.